DIGITAL MARKETING COMMUNICATION ANALYSIS JAWA POS RADAR SOLO - Rayhan Pahlevi, Haggi; Amborowati, Agustin (Jurnal Manajemen Bisnis dan Terapan, 2024)
Digital marketing communication has a crucial role in the modern marketing era. In this context, digital media is an effective means to reach a wider audience and promote products or services efficiently. This research aims to find out how the implementation of digital marketing communication in Jawa Pos Radar Solo. This research uses a case study research design with descriptive discussion method. By describing data from interviews, observations, and company documents from the object of research, namely the implementation of digital marketing communications at Jawa Pos Radar Solo through various media. So that it can be explained about the implementation of digital marketing communication in Jawa Pos Radar Solo. Jawa Pos Radar Solo has successfully implemented digital marketing communication through various channels, including online public relations, online partnership, interactive advertising, opt-in email marketing, and social media marketing with one-way and two-way communication approaches with full control. Jawa Pos Radar Solo follows the AIDA (Awareness, Interest, Desire, Action) digital marketing communication model in their strategy. The digital marketing communication media used include websites, display ads, email, social media, blogs, word of mouth, and mobile marketing. Despite its success in implementing digital marketing communication, Jawa Pos Radar Solo also faces some obstacles. So to overcome these obstacles, it is necessary to implement several strategies to improve the digital marketing communication of Jawa Pos Radar Solo.